2009
DOI: 10.1523/jneurosci.5977-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Direct Control of Peripheral Lipid Deposition by CNS GLP-1 Receptor Signaling Is Mediated by the Sympathetic Nervous System and Blunted in Diet-Induced Obesity

Abstract: We investigated a possible role of the central glucagon-like peptide (GLP-1) receptor system as an essential brain circuit regulating adiposity through effects on nutrient partitioning and lipid metabolism independent from feeding behavior. Both lean and diet-induced obesity mice were used for our experiments. GLP-1 (7-36) amide was infused in the brain for 2 or 7 d. The expression of key enzymes involved in lipid metabolism was measured by real-time PCR or Western blot. To test the hypothesis that the sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 54 publications
(57 reference statements)
10
135
2
1
Order By: Relevance
“…Moreover, others have demonstrated that acute activation of central nervous system (CNS) GLP-1Rs promotes BAT thermogenesis and WAT browning [36][37][38]. However, browning of WAT induced by CNS infusion of GLP-1R agonist was abolished in mice with diet-induced obesity [36,38]. We observed that chronic peripheral treatment with GLP-1R agonist promoted the browning of WAT in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, others have demonstrated that acute activation of central nervous system (CNS) GLP-1Rs promotes BAT thermogenesis and WAT browning [36][37][38]. However, browning of WAT induced by CNS infusion of GLP-1R agonist was abolished in mice with diet-induced obesity [36,38]. We observed that chronic peripheral treatment with GLP-1R agonist promoted the browning of WAT in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 57%
“…Our data A clinical study revealed that a dipeptidyl peptidase-4 (DPP-4) inhibitor that decreases endogenous GLP-1 degradation augmented adipose tissue lipolysis and the rate of systemic lipid oxidation in type 2 diabetic patients [35]. Moreover, others have demonstrated that acute activation of central nervous system (CNS) GLP-1Rs promotes BAT thermogenesis and WAT browning [36][37][38]. However, browning of WAT induced by CNS infusion of GLP-1R agonist was abolished in mice with diet-induced obesity [36,38].…”
Section: Discussionmentioning
confidence: 71%
“…Fat mobilization is normally mediated via increased activities of the SNS [31,32]. Increased release of NE from sympathetic nerves activates Adrb3 on the surface of adipocytes, increasing intracellular levels of cAMP that activates PKA, which mediates phosphorylation and activation of HSL [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Seven to 11 animals per group were used. Tenweek-old WT and TKO mice were obtained as previously described (13)(14)(15) …”
Section: Animals and Dietsmentioning
confidence: 99%